2018
DOI: 10.1111/eva.12638
|View full text |Cite
|
Sign up to set email alerts
|

Geographic isolation and larval dispersal shape seascape genetic patterns differently according to spatial scale

Abstract: Genetic variation, as a basis of evolutionary change, allows species to adapt and persist in different climates and environments. Yet, a comprehensive assessment of the drivers of genetic variation at different spatial scales is still missing in marine ecosystems. Here, we investigated the influence of environment, geographic isolation, and larval dispersal on the variation in allele frequencies, using an extensive spatial sampling (47 locations) of the striped red mullet (Mullus surmuletus) in the Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…Relatively few studies have evaluated the effect of asymmetric larval dispersal on spatial genetic patterns in marine species (Riginos et al, ). Perhaps not surprisingly, these studies, like our results here with A. tenuis and A. millepora, consistently uncover substantial asymmetries in inferred dispersal (Benestan et al, ; Dalongeville et al, ; Xuereb et al, ). Clearly, conventional analyses, especially those based on summary statistics like F ST where all directional information is obscured, will fail to uncover important elements regarding relationships among populations (Kool et al, ; Riginos et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Relatively few studies have evaluated the effect of asymmetric larval dispersal on spatial genetic patterns in marine species (Riginos et al, ). Perhaps not surprisingly, these studies, like our results here with A. tenuis and A. millepora, consistently uncover substantial asymmetries in inferred dispersal (Benestan et al, ; Dalongeville et al, ; Xuereb et al, ). Clearly, conventional analyses, especially those based on summary statistics like F ST where all directional information is obscured, will fail to uncover important elements regarding relationships among populations (Kool et al, ; Riginos et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Geographic surveys of intraspecific genetic variation can provide important insights regarding dispersal (Hellberg, ; Riginos & Liggins, ; Selkoe, D'Aloia, et al, ) and indeed several studies have considered predictions arising from biophysical dispersal models alongside observed spatial genetic patterns, typically for coastal marine taxa. Although some individual studies report correlations (Benestan et al, ; Dalongeville et al, ; Foster et al, ; Galindo, Olson, & Palumbi, ; Schunter et al, ; Thomas et al, ; Truelove et al, ; White et al, ; Xuereb et al, ), a recent review of the field found only moderate to low concordance between biophysical predictions and empirical genetic patterns (Selkoe, Scribner, & Galindo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial predictor variables were extracted as dbMEM variables following Borcard and Legendre (). Dalongeville et al () provides an example detailing the process. To construct dbMEM variables, first a pairwise geographic distance matrix was created, using haversine distances between all pairs of the 58 sample locations, with the package geosphere version 1.5‐5 in r (Hijmans, ).…”
Section: Methodsmentioning
confidence: 99%
“…We apply a method proposed by Legendre, Fortin, and Borcard (2015) to SNP data obtained by genotyping-by-sequencing to isolate signals of spatial autocorrelation from HAD. The method uses distancebased Moran's eigenvector mapping (dbMEM), formally known as principal coordinates of neighbour matrices (Borcard & Legendre, 2002;Borcard, Legendre, Avois-Jacquet, & Tuomisto, 2004;Dray, Legendre, & Peres-Neto, 2006), to account for spatial autocorrelation associated with the distribution of sample sites and ultimately construct regression variables summarizing spatial structure (Dalongeville et al, 2018). These explanatory spatial variables then are used in canonical analysis, such as redundancy analysis (RDA), along with other environmental predictors to identify the proportion of variation due to spatial and environmental factors (Borcard et al, 2004).…”
Section: Inherent Variation In the Dispersion Of Sample Sites Can Leamentioning
confidence: 99%